(untitled) (Global Journal of Science Frontier Research, 2015)
The author establish a set of four presumbaly new results which depict the interrelationship between Infinite Product Identities, Continued-Fraction Identities and Combinatorial Partition Identities. Several closely related q-identities such as (for example) Jacobi’s tripleproduct identity are also considered.